The short and long term effects of contingent Aversive Noise on Stuttering - MN, Hegde (Journal of All India Institute of Speech and Hearing, 1971)
Modification of behaviour through aversive conditioning has had a history of a few decades. The early and also most frequent use of aversive conditioning has been in the problem areas of alcoholism and sexual disorders (Eysenck and Rachman, 1965). However, the application of aversive conditioning techniques to stuttering has been a recent affair, although the first published report appeared in 1937 (Van Riper, 1937).